2019
DOI: 10.1111/eje.12455
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives of early and gradual transitioning between simulation and clinical training in dentistry and their suggestions for future course improvements

Abstract: Introduction:Students' perspectives on their learning environment are essential for course development and to enhance the educational experience. In dentistry, there is limited understanding of how students perceive their early clinical training. This study presents students' views on their gradual progression from simulation to patient care and describes the approaches they followed to adapt during this transitioning phase.Methods: A qualitative study design was employed, drawing on focus group discussions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…This approach is contrary to advice encouraging selected referral for VPT to a specialist environment (Komabayashi & Zhu 2010), but that may depend on a number of country-specific factors. In a deviation from students surveyed in other studies (Botelho et al 2018, Kashbour et al 2019, this cohort did not report a lack of knowledge, perhaps as they were more advanced in their studies, or alternatively because they did not wish to admit a lack of knowledge in front of their peers. In the same way, none of them mentioned personal alternative strategies to deal specifically with the stress of deep caries treatment or stress management in general.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This approach is contrary to advice encouraging selected referral for VPT to a specialist environment (Komabayashi & Zhu 2010), but that may depend on a number of country-specific factors. In a deviation from students surveyed in other studies (Botelho et al 2018, Kashbour et al 2019, this cohort did not report a lack of knowledge, perhaps as they were more advanced in their studies, or alternatively because they did not wish to admit a lack of knowledge in front of their peers. In the same way, none of them mentioned personal alternative strategies to deal specifically with the stress of deep caries treatment or stress management in general.…”
Section: Discussionmentioning
confidence: 62%
“…In these circumstances, students within this study reported coping by enlisting the initial support or the help of their peers and colleagues, who they are more comfortable with, rather than engaging with the supervisor. Although this peer support is recognized as a factor of confidence, and peer mentoring is developed in some dental universities (Kashbour et al 2019), it is arguably not sufficient within undergraduate clinical teaching and the students would prefer more feedback directly from their supervisors, rather than just a grade or a short comment. It was previously shown that the quantity and quality of feedback were positive predictors of students' autonomous motivation (Orsini et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations